When and how disease‐modifying drugs for multiple sclerosis should be changed in daily practice. Issue 1 (February 2017) - Shimizu, Yuko; Ikeguchi, Ryotaro; Kitagawa, Kazuo
Abstract: In Japan, four classes and five kinds of disease‐modifying drugs (DMD), such as interferon‐beta (IFNβ1a and IFNβ1b), glatiramer acetate, fingolimod and natalizumab, are approved as curative treatments for multiple sclerosis. There are advantages and disadvantages of each of these DMD, and treatment guidelines for escalation and induction therapy have yet to be established. Escalation therapy starts with a first‐line DMD, and when the first‐line DMD does not provide optimal efficacy, therapy involves a step‐up to a second DMD. Induction therapy supports the early use of a highly effective second DMD for the purpose of long‐term maintenance treatment. The DMD can be separated by their treatment efficacy and long‐term safety. Because of their demonstrated long‐term safety and efficacy, the drugs of choice are first‐line DMD (IFNβ and glatiramer acetate). In addition, their long‐term administration has not been associated with malignancies, opportunistic infections, secondary immune disease or fetal toxicity. Though fingolimod and natalizumab have been shown to have high efficacy, their long‐term safety has not been established; thus, they are used as second‐line therapies. The physician sometimes has to consider switching DMD when treating multiple sclerosis patients. The reasons for changing treatment are lack of efficacy, intolerability, adverse effects, cost, pregnancy, incorrect diagnosis and disease stability. The present review provides a general introduction to the most recent findings to help practitioners determine when and how DMD treatment should be changed for multiple sclerosis. Abstract : This review provides a general introduction to the most recent findings to help practitioners determine when and how DMD treatment should be changed for multiple sclerosis.